Impact of stroke volume on motor outcome in neonatal arterial ischemic stroke. (March 2020) - Wiedemann, Andreas; Pastore-Wapp, Manuela; Slavova, Nedelina; Steiner, Leonie; Weisstanner, Christian; Regényi, Mária; Steinlin, Maja; Grunt, Sebastian; ,
Abstract: Background and objectives: Neonatal arterial ischemic stroke (NAIS) can lead to long-term neurological consequences such as cerebral palsy (CP). The aim of this study was to evaluate the predictive value of acute diffusion-weighted imaging (DWI) for CP by analyzing stroke volume next to brain structure involvement. Methods: We included 37 term-born infants with NAIS prospectively registered in a nationwide pediatric stroke registry. DWI was performed between 0 and 8 days (mean 3 days) after stroke manifestation. Participants were neurologically assessed at the age of 2 years. We calculated the stroke volume (in mm 3 ) and the ratio of the stroke volume to the volume of the entire brain (relative stroke volume). The predictive value of the relative stroke volume was analyzed and an optimal threshold for classification of children with high- and low-rates of CP was calculated. Predictive value of brain structure involvements and the prevalence of CP in combinations of different brain structures was also assessed. Results: Sixteen children (43.2%) developed CP. Relative stroke volume significantly predicted CP (p < .001). Its optimal threshold for division into high- and low-rate of CP was 3.3%. The basal ganglia (OR 8.3, 95% CI 1.2–60.0) and basis pontis (OR 18.5, 95% CI 1.8–194.8) were independently associated with CP. Conclusion: In addition to determining the involvement of affected brain areas, the volumetric quantification of stroke volume allows accurate prediction of cerebral palsy in newborns with NAIS. Highlights: The exact determination of the lesion volume in newborns with an ischemic stroke allows a prognosis of later cerebral palsy. The involvement of vulnerable regions such as basal ganglia and corticospinal tract is associated with poor motor prognosis. Small strokes can co-affect multiple vulnerable brain structures with a high-risk of cerebral palsy.